2022
DOI: 10.2147/ppa.s378335
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Suboptimal Adherence Identified by Patient-Reported Outcomes Assessments in Routine HIV Care at 2 North American Clinics

Abstract: Use of patient-reported outcomes assessments (PROs) can improve patient-provider communication and focus provider attention on current health issues. This analysis examines the association between suboptimal antiretroviral therapy (ART) adherence and factors obtained through PROs among people with HIV (PWH) at 2 North American outpatient clinics. Patients and Methods: Immediately before a clinic visit, PWH completed self-administered PROs. Unadjusted and adjusted odds ratios (ORs) and 95% confidence intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Despite the simplicity and convenience of using INSTI-STRs, our findings indicate that some patients may not be optimally treated, highlighting the need for refinement in treatment strategies. A previous study reported that the burden regarding medication was associated with poor medication adherence [ 18 ]. Our results emphasize the importance of identifying patients’ needs and dissatisfaction with ARVs, as well as their ART adherence, in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the simplicity and convenience of using INSTI-STRs, our findings indicate that some patients may not be optimally treated, highlighting the need for refinement in treatment strategies. A previous study reported that the burden regarding medication was associated with poor medication adherence [ 18 ]. Our results emphasize the importance of identifying patients’ needs and dissatisfaction with ARVs, as well as their ART adherence, in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants with <90% adherence withdrew for nonvirologic reasons in both the week 48 7 and week 144 analyses, suggesting that participants with lower adherence have higher attrition in the long-term trial and were either lost to follow-up or withdrew consent. Ensuring that people living with HIV are satisfied with their ART may improve adherence; 10 however, treatment satisfaction and other parameters potentially associated with adherence are not always measured in randomized clinical trials. This highlights the need for further studies to translate adherence factors from clinical trials to real-world practice.…”
Section: Discussionmentioning
confidence: 99%